The Unauthorised Commercial Use of Person's Voice in AI - Messo, Waltteri (My University, 2026)
This thesis examines the unauthorised commercial use of the human voice in the context of generative artificial intelligence (AI) and addresses the research question: To what extent can copyright law and human rights frameworks effectively protect individuals from the unauthorised commercial use of their voice in AI-generated content? This thesis aims to answer this question by analysing the structural limitations of international copyright law and the potential of human rights instruments when a person's voice is cloned using emerging technologies and used commercially without authorisation. The study highlights the vulnerability of both public figures and ordinary citizens as technology outpaces current regulations. Thesis aims to provide considerations for legislators regarding the necessity of stricter binding rules and the potential adoption of a sui generis right of publicity. The research uses legal dogmatics and critical legal studies as methods, approaching the topic from a human rights perspective. The primary sources of international law include treaties such as the Berne Convention, the TRIPS Agreement, and the European Convention on Human Rights. The main source of the case law is the European Court of Human Rights, particularly cases regarding the protection of privacy, private life, freedom of expression, and property, which form the basis of the protection framework presented in the thesis. The findings indicate that while international copyright law is ineffective in protecting the human voice itself due to the fixation requirement, the human rights framework regarding the right to private life can be interpreted to protect the voice as personal data and an aspect of personality. However, current frameworks are insufficient, and the international community needs to consider establishing regulations, such as a specific right of publicity, to ensure adequate protection of personal identity and traits in the AI era.

--- Tässä tutkielmassa tarkastellaan ihmisäänen luvatonta kaupallista käyttöä generatiivisen tekoälyn (AI) kontekstissa ja vastataan tutkimuskysymykseen: Missä määrin tekijänoikeuslainsäädäntö ja ihmisoikeussäännökset voivat tehokkaasti suojella yksilöitä heidän äänensä luvattomalta kaupalliselta käytöltä tekoälyllä luodussa sisällössä? Tutkielman tavoitteena on vastata tähän kysymykseen analysoimalla kansainvälisen tekijänoikeuslainsäädännön rakenteellisia rajoituksia ja ihmisoikeussopimusten tarjoamia mahdollisuuksia tilanteissa, joissa henkilön ääni kloonataan uutta teknologiaa hyödyntäen ja sitä käytetään kaupallisesti ilman lupaa. Tutkimus tuo esiin sekä julkisuuden henkilöiden että tavallisten ihmisten haavoittuvuuden, kun teknologinen kehitys etenee nykyistä sääntelyä nopeammin. Tutkielman tarkoituksena on tarjota lainsäätäjille näkökohtia tiukempien sitovien sääntöjen tarpeellisuudesta sekä mahdollisuudesta hyödyntää erillistä sui generis -tyyppistä right of publicity -sääntelyä. Tutkimusmenetelminä käytetään oikeusdogmatiikkaa ja kriittistä oikeusteoriaa, ja aihetta lähestytään ihmisoikeusnäkökulmasta. Kansainvälisen oikeuden ensisijaiset lähteet koostuvat sopimuksista, kuten Bernin yleissopimus, TRIPS-sopimus ja Euroopan ihmisoikeussopimus. Keskeisimpänä oikeuskäytännön lähteenä käytetään Euroopan ihmisoikeustuomioistuimen oikeuskäytäntöä, ja erityisesti tuomioita koskien yksityisyyden, yksityiselämän, sananvapauden ja omaisuuden suojaa, mitkä muodostavat tutkielmassa esitettävän suojakehyksen perustan. Tulokset osoittavat, että vaikka kansainvälinen tekijänoikeuslainsäädäntö on tehoton suojaamaan ihmisääntä itsessään aineellisen muodon vaatimuksen vuoksi, ihmisoikeussäännöksiä ja oikeutta yksityiselämään voidaan tulkita siten, että ne suojaavat ääntä henkilötietona ja osana persoonallisuutta. Nykyiset sääntelykehykset ovat kuitenkin riittämättömiä, ja kansainvälisen yhteisön on harkittava esimerkiksi erityisen right of publicity -sääntelyn luomista varmistaakseen henkilökohtaisen identiteetin ja piirteiden riittävän suojan tekoälyn aikakaudella.
Keywords: artificial intelligence, voice cloning, copyright law, human rights, ECHR, personality rights, right of publicity, technology, fixation